Pelatihan Pengembangan Usaha Barista Dan Mixologi Untuk Siswa-Siswi Di SMK Al-Azhar Batam - Moh. Thandzir; Haufi Sukmamedian; Syailendra Reza I. R; Natal Olotua Sipayung; Dailami (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
Barista training is an important investment in the development of the coffee industry to improve the quality of their products and services. A good barista, apart from being able to mix delicious coffee, must be able to make customers feel satisfied with their service. That way, customers will be more loyal to your coffee shop. The more satisfied they are, the more often they will visit your coffee shop. That way, your coffee shop's turnover and income will increase. However, in general mixology is considered a comprehensive and in-depth study of the art and skill of mixing drinks. More specifically, Bar School states that mixologist refers to a profession involved in making cocktails, creating new drinks and techniques based on extensive knowledge of all existing ingredients as well as a deep understanding of the history of drinks. Meanwhile, the term bartender refers to individuals who are able to translate and realize these techniques and concepts practically. Usually a bartender plays a direct role at the bar, serving and interacting with customers, and if necessary, interpreting customer needs regarding the desired drink.